The Use of Speech Acts for Strategic Social Media Branding in Instagram Captions - Adillah, Risa Firli (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2025)
ABSTRACT: In the rapidly evolving digital landscape, brand communication has undergone a notable shift towards digital platforms, primarily leveraging social media channels like Instagram. This study delves into the strategic use of speech acts to shape branding strategies, specifically examining the Instagram captions of @brookibakehouse. Employing a qualitative content analysis methodology, this research scrutinizes the deliberate deployment of speech acts. The findings reveal that among the 162 post captions analyzed, a substantial portion included speech acts, with 78 characterized by assertive speech acts, 65 incorporating directive speech acts, and 24 featuring expressive acts. This analysis highlights the multifaceted role of speech acts, serving as a critical element in crafting the brand's image, honing engagement tactics, and fostering meaningful connections with the audience across diverse social media platforms.   Keywords: Speech Act; Illocutionary Act; Social media; Online branding; Brand’s image